Interaction mechanism and intervention strategy between metabolic dysfunction-associated steatotic liver disease and intestinal microbiota - Yang, Wentai; Jin, Qing; Xiao, Dewang; Li, Xiang; Huang, Defa (Frontiers in Microbiology, 2025)
The interaction between metabolic dysfunction-associated seatotic liver disease (MASLD) and gut microbiota regulates hepatic metabolic homeostasis through the gut-liver axis, and its mechanisms involve intestinal dysbiosis (decreased bacteroidetes, increased ratio of firmicutes/proteobacteria), bile acid metabolism reprogramming (secondary bile acids inhibit FXR signaling), short-chain fatty acid (SCFAs) deficiency, and endotoxin-mediated inflammatory activation (TLR4/NF-κB pathway). Among the intervention strategies, probiotics (such as Bifidobacteria) improved inflammation by regulating microbiota structure and intestinal barrier function, prebiotics such as resistant starch enriched butyric acid-producing bacteria and reduced liver lipid deposition, fecal microbiota transplantation (FMT) could remodel the microbiota but needed to optimize safety, restricted fructose intake and Mediterranean diet reduced liver damage by regulating microbiota metabolism, and metabolic surgery improved fibrosis through microbiota remodeling and bile acid signaling. In the future, it is necessary to combine multi-omics technology to analyze the microbiota-host interaction network, develop precision therapies such as phage targeted clearance or engineering bacterial delivery of metabolites, and promote the clinical transformation of personalized intervention programs.